Polyethylenimine based magnetic nanoparticles mediated non-viral CRISPR/Cas9 system for genome editing - Rohiwal, S S; Dvorakova, N; Klima, J; Vaskovicova, M; Senigl, F; Slouf, M; Pavlova, E; Stepanek, P; Babuka, D; Benes, H; Ellederova, Z; Stieger, K (Scientific reports, 2020)
Clustered regularly interspaced short palindromic repeats-associated protein (CRISPR/Cas9) system has become a revolutionary tool for gene editing. Since viral delivery systems have significant side effects, and naked DNA delivery is not an option, the nontoxic, non-viral delivery of CRISPR/Cas9 components would significantly improve future therapeutic delivery. In this study, we aim at characterizing nanoparticles to deliver plasmid DNA encoding for the CRISPR-Cas system in eukaryotic cells in vitro. CRISPR/Cas9 complexed polyethylenimine (PEI) magnetic nanoparticles (MNPs) were generated. We used a stable HEK293 cell line expressing the traffic light reporter (TLR-3) system to evaluate efficient homology- directed repair (HDR) and non-homologous end joining (NHEJ) events following transfection with NPs. MNPs have been synthesized by co-precipitation with the average particle size around 20 nm in diameter. The dynamic light scattering and zeta potential measurements showed that NPs exhibited narrow size distribution and sufficient colloidal stability. Genome editing events were as efficient as compared to standard lipofectamine transfection. Our approach tested non-viral delivery of CRISPR/Cas9 and DNA template to perform HDR and NHEJ in the same assay. We demonstrated that PEI-MNPs is a promising delivery system for plasmids encoding CRISPR/Cas9 and template DNA and thus can improve safety and utility of gene editing.
Keywords: polyethylenimin; velikost částic; CRISPR-Cas systémy; Gene Transfer Techniques; HEK293 Cells; CRISPR-Cas Systems; statická elektřina; Particle Size; transfekce; reportérové geny; Polyethyleneimine; Transfection; lidé; fluorescenční protilátková technika; chemické jevy; editace genu; Fluorescent Antibody Technique; Magnetite Nanoparticles; technika přenosu genů; Gene Editing; koloidy; HEK293 buňky; Chemical Phenomena; plazmidy; Gene Expression; exprese genu; Cell Survival; Plasmids; Genes, Reporter; viabilita buněk; magnetické nanočástice; Static Electricity; Colloids; Humans